A Robust Static Headspace GC-FID Method to Detect and Quantify Formaldehyde Impurity in Pharmaceutical Excipients - Bashir Daoud Agha Dit Daoudy; Mohammad Ammar Al-Khayat; Francois Karabet; Mohammad Amer Al-Mardini (Journal of Analytical Methods in Chemistry)
Formaldehyde is a highly reactive impurity that can be found in many pharmaceutical excipients. Trace levels of this impurity may affect drug product stability, safety, efficacy, and performance. A static headspace gas chromatographic method was developed and validated to determine formaldehyde in pharmaceutical excipients after an effective derivatization procedure using acidified ethanol. Diethoxymethane, the derivative of formaldehyde, was then directly analyzed by GC-FID. Despite the simplicity of the developed method, however, it is characterized by its specificity, accuracy, and precision. The limits of detection and quantification of formaldehyde in the samples were of 2.44 and 8.12 µg/g, respectively. This method is characterized by using simple and economic GC-FID technique instead of MS detection, and it is successfully used to analyze formaldehyde in commonly used pharmaceutical excipients.